Integration of Social Finance in the Economic Empowerment of Generation Z as an Inclusive Employment Solution - Hendri Al Farouk; Yazid Aris Fuadi (Fakultas Dakwah UIN KHAS Jember, 2025)
Generation Z (Gen Z) in the Organization of Islamic Cooperation (OIC) countries faces challenges related to high NEET (Not in Education, Employment, or Training) rates due to a mismatch between skills and labor market demands, limited access to capital, and a lack of inclusive job opportunities. Meanwhile, the potential of Islamic social finance (Zakat, Waqf) and the growth of digital platforms remain underutilized in empowering youth. This research explores the role of platforms such as Coursera/Udemy in promoting the financial integrity of Gen Z and creating jobs. Additionally, it examines the role of dropshipping on Tokopedia and Trendyol in enhancing the financial integrity of Gen Z and creating job opportunities. The study adopts a mixed-methods approach, including case studies of Zakat-based digital training programs in Indonesia and Turkey, a survey of 150 Gen Z entrepreneurs engaged in dropshipping on Souq, Tokopedia, and Trendyol, and secondary data analysis from social financial institutions and e-commerce platforms. Results show that 72% of Coursera/Udemy participants funded by Zakat successfully started dropshipping businesses, with an average income increase of 35%. Collaboration between Waqf institutions and Trendyol has created 500 jobs for Gen Z in rural areas of Turkey. The main challenges include the digital literacy gap (45% of participants in remote areas) and e-commerce regulations that do not fully support Sharia-compliant SMEs. This study recommends policy synergies between OIC governments, social financial institutions, and digital platforms to expand Zakat/Waqf-based training schemes and facilitate Gen Z's access to an inclusive e-commerce ecosystem.